2013
DOI: 10.1098/rspb.2012.2916
|View full text |Cite
|
Sign up to set email alerts
|

Is the continental life of the European eel Anguilla anguilla affected by the parasitic invader Anguillicoloides crassus ?

Abstract: Quantifying the fitness cost that parasites impose on wild hosts is a challenging task, because the epidemiological history of field-sampled hosts is often unknown. In this study, we used an internal marker of the parasite pressure on individual hosts to evaluate the costs of parasitism with respect to host body condition, size increase and reproductive potential of field-collected animals for which we also determined individual age. In our investigated system, the European eel Anguilla anguilla and the parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 54 publications
4
46
0
Order By: Relevance
“…But this criterion is not the best reflecting the eel pathogenicity due to the short life cycle of A. crassus , and severely damaged swimbladders are shown to harbor very few or even no living nematodes [42, 63]. Nevertheless, using the Swimbladder Degenerative Index, Lefebvre et al [44] recently demonstrated that the most affected eels had greater body length and mass (+11% and +41% respectively) than unaffected eels of the same age. Despite these surprising counterintuitive results, high virulence and severe impacts of A. crassus are expected because A. anguilla lacks an adaptive immune response, and various pathogenic potentially lethal effects (e.g., anemia, energy drain, swimming performance decrease) have been demonstrated, threatening the success of spawning migration in the Sargasso Sea [35, 43, 44, 53, 58].…”
Section: Discussionmentioning
confidence: 99%
“…But this criterion is not the best reflecting the eel pathogenicity due to the short life cycle of A. crassus , and severely damaged swimbladders are shown to harbor very few or even no living nematodes [42, 63]. Nevertheless, using the Swimbladder Degenerative Index, Lefebvre et al [44] recently demonstrated that the most affected eels had greater body length and mass (+11% and +41% respectively) than unaffected eels of the same age. Despite these surprising counterintuitive results, high virulence and severe impacts of A. crassus are expected because A. anguilla lacks an adaptive immune response, and various pathogenic potentially lethal effects (e.g., anemia, energy drain, swimming performance decrease) have been demonstrated, threatening the success of spawning migration in the Sargasso Sea [35, 43, 44, 53, 58].…”
Section: Discussionmentioning
confidence: 99%
“…However, the most serious damage is on the swimbladder itself. The infection may alter the gas composition of the swimbladder, block the pneumatic duct, impairing the organ's function (Kirk, Lewis, et al., ; Lefebvre et al., ) leading to necrosis in the most extreme cases (Molnár, Székely, & Perényi, ; Würtz & Taraschewski, ). The alteration of the swimbladder has a direct impact on swimming capacity (Sprengel & Lüchtenberg, ; Székely, Palstra, Molnár, & van den Thillart, ).…”
Section: Component 4—alien Species: Effects Of Alien Parasitoid Anguimentioning
confidence: 99%
“…More active fish may consume more paratenic hosts and increase the probability of A . crassus infection (Lefebvre et al ., ).…”
Section: Discussionmentioning
confidence: 97%